2021
DOI: 10.1111/ipd.12802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ankyloglossia and tongue‐tie division on speech articulation: A systematic review

Abstract: Aim Ankyloglossia is a common congenital malformation characterized by a short, thick, or tight tongue frenulum, and its effect on speech articulation remains controversial. This study aimed to evaluate (a) the association between ankyloglossia and speech disorders, and (b) the effectiveness of surgical interventions on the articulation of patients with ankyloglossia. Material and Methods A comprehensive search of PubMed was conducted. Randomized control trials (RCTs), cohort studies, case‐control studies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…To date, however, the exact relationship among these disorders is currently controversial due to the complexity of their etiology and diagnosis [ 27 , 34 ]. Ankyloglossia was found to be a risk factor for phonetic issues, while, according to the literature, there is no clear connection between a short lingual frenulum and speech problems, mainly due to a lack of a uniform lingual frenulum grading system and standardized clinical studies evaluating the effects of surgical treatment on speech articulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, the exact relationship among these disorders is currently controversial due to the complexity of their etiology and diagnosis [ 27 , 34 ]. Ankyloglossia was found to be a risk factor for phonetic issues, while, according to the literature, there is no clear connection between a short lingual frenulum and speech problems, mainly due to a lack of a uniform lingual frenulum grading system and standardized clinical studies evaluating the effects of surgical treatment on speech articulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Regarding the anatomic aspects quantitatively assessed in this instrument, Marchesan (2010) described the options for classifying the shape of the tip of the tongue, as well as the attachment site of the frenulum on the ventral aspect of the tongue and on the floor of the mouth. 14 In turn, a thick lingual frenulum has previously been considered as altered, 22 which, although controversial, is quantitatively assessed in our proposal, mainly for surgical concerns. As for the frenulum attachment form (punctiform or fan-shaped), we consider its evaluation to be important since it may influence surgical considerations due to the greater number of fibers observed in a fan-shaped attachment form.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is important to inquire about a history of speech difficulties in addition to a qualitative assessment upon functional examination. However, a systematic review reported little association between ankyloglossia and speech disorders, so more widely accepted universal scoring systems and well-designed clinical studies are still needed 22 . In this regard, proposals for protocols that look at speech characteristics with the same parameters will help to address these controversies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to the best of our knowledge just two studies of Ito et al [18] and Dollberg et al [21] were conducted in non-English language [18,21] which may limit the generalizability of the results. So, as highlighted in a systematic review by Wang et al [22], there is a need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%